Pengaruh Kinerja Lingkungan, Good Corporate Governance, dan Kepemilikan Asing Terhadap Nilai Perusahaan Manufaktur - Rahayu, Ni Luh Dina; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p01, 2019)
The purpose of this study was to determine the effect of environmental performance (PROPER rating), GCG mechanism, and foreign ownership on company value. The sample in this study is a manufacturing company listed on the Stock Exchange in 2013-2017 with a total of 34 companies, environmental performance seen from the PROPER rating achieved by the company, Tobin’s Q to measure corporate value and proxy for GCG obtained using factor analysis. The data analysis technique of this study uses multiple linear analysis. Based on the results of the analysis it was found that environmental performance and foreign ownership had a positive effect on firm value. This indicates that the higher the percentage of foreign ownership and PROPER ratings obtained by manufacturing companies, the higher the value of the company. The mechanism of Good Corporate Governance is stated to have no effect on the value of the company. Keywords : Environmental Performance; Company Value; Good Corporate Governanc; Foreign Ownership.